Higher Adalimumab Levels Are Associated with Histologic and Endoscopic Remission in Patients with Crohn's Disease and Ulcerative Colitis. Issue 2 (11th January 2016) - Yarur, Andres J.; Jain, Anjali; Hauenstein, Scott I.; Quintero, Maria A.; Barkin, Jamie S.; Deshpande, Amar R.; Sussman, Daniel A.; Singh, Sharat; Abreu, Maria T.
Abstract : Background: Optimal levels of adalimumab (ADA) have not been defined according to the ultimate goal of inflammatory bowel disease treatment—histologic and/or endoscopic healing. The aim of this study was to assess the relationship between random serum ADA levels and histologic and endoscopic healing in patients with inflammatory bowel disease. Methods: This was a cross-sectional study including 66 patients receiving maintenance therapy with ADA for Crohn's disease or ulcerative colitis. ADA levels and anti-adalimumab antibodies (AAA) were measured at the time of colonoscopy. The primary outcome was histologic healing (lack of endoscopic and histologic inflammation) and the secondary outcomes were endoscopic healing and serum levels of C-reactive protein, tumor necrosis factor, ICAM, VCAM, and interleukins 1β, 6, and 8. Results: Sixty-six patients (59 with Crohn's disease) were included. Mean random ADA levels were significantly lower in patients with histologic and endoscopic inflammation (9.2 [SD: 8.4] versus 14.1 [6.4] μg/mL, P = 0.03 and 8.5 [SD: 7.8] versus 13.3 [SD: 7.7], P = 0.02, respectively). The ADA level that was best associated with histologic healing was 7.8 μg/mL (receiver operating characteristic: 0.76 [ P = 0.04]), whereas the ADA level that was best associated with endoscopic healing was 7.5 μg/mL (receiver operating characteristic: 0.73 [ P = 0.02]). The presence of AAA was associated with lower random ADA levels (5.7 versus 12.5 μg/mL, P = 0.002) and higher C-reactive protein levels (30.3 versus 12.0, P = 0.01). Conclusions: Achievement of histologic and endoscopic healing may require higher levels of ADA than previously described for endoscopic remission. The measurement of random ADA levels and anti-drug antibodies may guide therapy and edify the course of incomplete responses.